PENERAPAN SCHOOLOGY SEBAGAI LEARNING MANAGEMENT SYSTEM BAGI GURU SMAN 1 SUTERA - Jefril Rahmadoni; Adi Arga Arifnur; Ullya Mega Wahyuni (Jurnal Hilirisasi IPTEKS, 2020)
This community service aims to provide more practical, innovative and efficient learning methods that are adapted to the development of information technology in the era of the industrial revolution 4.0 by utilizing the free Learning Management System (LMS) media, namely Schoology. The learning process in this LMS combines some content in one application that is packaged in an interactive form such as flash or animation, learning videos, assignments and examinations with various features including course content which includes articles, module materials. Therefore, we from the Andalas University Information Systems Study Program aim to socialize the utilization of information technology in the teaching and learning process with LMS Schoology at SMAN 1 Sutera. As the best school in Pesisir Selatan District, SMAN 1 Sutera has been equipped with facilities to support teaching and learning processes that can utilize information technology. The subjects of this dedication are all the teachers of SMAN 1 Sutera, where the teachers are given training in the use of Schoology in order to be able to apply the learning process based on information technology. The method of carrying out this activity is carried out in five stages: initial survey, planning, preparation, training and evaluation. During the training, the enthusiasm of the teacher was quite high by giving a positive response of 90% of the participants and responding that Schoology was another alternative for an interesting learning process. And the rest are not yet accustomed to using technology in the learning process due to age.